Cooperatives own part of the Web - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Since 30 January 2002, cooperative organisations can register their own address on the Internet. Instead of being a so-called dot.com, or dot.org, they can be a dot.coop. Among the pre-registered coops are fruit producers in the Caribbean, dairy...